2020
DOI: 10.3390/metabo10090358
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomics Analysis on Obstructive Sleep Apnea Patients after Multilevel Sleep Surgery

Abstract: Background: Obstructive sleep apnea (OSA) is caused by partial or complete obstruction of the upper airways. Corrective surgeries aim at removing obstructions in the nasopharynx, oropharynx, and hypopharynx. OSA is associated with an increased risk of various metabolic diseases. Our objective was to evaluate the effect of surgery on the plasma metabolome. Methods: This study included 39 OSA patients who underwent Multilevel Sleep Surgery (MLS). Clinical and anthropometric measures were taken at baseline and fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Patients with OSA usually have abnormal metabolism of glucose and lipids. Though obesity is one of the main risk factors of OSA, many investigations have shown that OSA can have an independent effect on dyslipidemia as well as obesity ( Karkinski et al, 2017 ; Silva et al, 2018 ; Alterki et al, 2020 ). In non-obese patients, OSA could aggravate abnormal lipid metabolism ( Karkinski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with OSA usually have abnormal metabolism of glucose and lipids. Though obesity is one of the main risk factors of OSA, many investigations have shown that OSA can have an independent effect on dyslipidemia as well as obesity ( Karkinski et al, 2017 ; Silva et al, 2018 ; Alterki et al, 2020 ). In non-obese patients, OSA could aggravate abnormal lipid metabolism ( Karkinski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that after eliminating interference factors, only severe OSA had an independent association with dyslipidemia ( Martínez-Cerón et al, 2021 ). Treatment with OSA, either multilevel sleep surgery or continuous positive airway pressure (CPAP) therapy, has a positive impact on the metabolic status ( Alterki et al, 2020 ; Simon et al, 2020 ). So, the question is, which key factors through what signaling pathways contribute to abnormal lipid metabolism in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…It can provide insight into the metabolic processes and pathogenesis of human diseases from a systematic perspective. A few studies used this approach to study the association between OSA and the change of metabolites (Ferrarini et al, 2013;Xu et al, 2016;Alterki et al, 2020;Humer et al, 2020;Reutrakul et al, 2021). Ferrarini et al (2013) collected plasma samples of 33 OSA patients and analyzed them with LC-QTOF-MS.…”
Section: Discussionmentioning
confidence: 99%
“…The study population was diagnosed using Type I PSG test as detailed [ 29 ]. This test involves an overnight sleep in a sleep lab, during which biophysiological data was captured to formulate a comprehensive picture of participants' sleep architecture.…”
Section: Methodsmentioning
confidence: 99%